ANALISIS 5S DALAM PROSES PRODUKSI DI PT. XYZ - editor1; Ahmat Nur Alim (Fakultas Teknik dan Rekayasa, 2022)
PT. Xyz is engaged in manufacturing spare parts. Based on the observations of PT. Xyz found that the company had not implemented the 5S working principle properly. Kaizen 5S is a method of structuring and maintaining an intensive work area originating from Japan that is used by management in an effort to maintain order, efficiency and discipline at work sites while improving overall company performance. The conclusions that can be obtained from research on the implementation of the 5S method in improving the work area that have been carried out are as follows: evaluation of the 5S program on the production floor of PT. Xyz has not been fully maximized, the role of the team leader is an important key for the successful implementation of the 5S method, the factors that influence the unsuccessful application of the 5S method are the employees' understanding of the 5S function, motivation, team head performance and supervision of the 5S method implementation. Knowing the implementation of the 5S program at PT. Xyz. The implementation of the 5S program is good, the program is carried out between working hours, 10 minutes before enough the job . In its application, it creates a clean and tidy environment, can simplify and speed up the production process, and extend the life of production machines, due to routine inspection and maintenance activities. The strategy for improving the application of the 5S method recommended for the 5S program in the production area is periodic monitoring of the implementation of 5S and work instructions that operators must carry out 5S.